2020
DOI: 10.1111/ajt.15687
|View full text |Cite
|
Sign up to set email alerts
|

Pseudomonas aeruginosa and acute rejection independently increase the risk of donor-specific antibodies after lung transplantation

Abstract: Factors contributing to donor‐specific HLA antibody (DSA) development after lung transplantation have not been systematically evaluated. We hypothesized that the isolation of Pseudomonas aeruginosa in respiratory specimens would increase the risk of DSA development. Our objective was to determine the risk of DSA development associated with the isolation of Pseudomonas aeruginosa after lung transplantation. We conducted a single‐center retrospective cohort study of primary lung transplant recipients and examine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
26
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(30 citation statements)
references
References 57 publications
(162 reference statements)
2
26
2
Order By: Relevance
“…In patients suffering from CF, airway-colonizing bacteria and their antibiotic sensitivity are perfectly known prior to transplantation, resulting usually in an effective and comfortable therapeutic management. On the other hand, the re-colonization can be particularly alarming, considering that the very isolation of Pseudomonas aeruginosa is considered an independent factor associated with an increased risk of developing DSA [ 6 ]. More importantly, we had to deal with the COVID-19 outbreak, which escalated in this time frame, considering how it presents high unresponsive fever and lung involvement as the most frequent symptoms.…”
Section: Discussionsupporting
confidence: 92%
“…In patients suffering from CF, airway-colonizing bacteria and their antibiotic sensitivity are perfectly known prior to transplantation, resulting usually in an effective and comfortable therapeutic management. On the other hand, the re-colonization can be particularly alarming, considering that the very isolation of Pseudomonas aeruginosa is considered an independent factor associated with an increased risk of developing DSA [ 6 ]. More importantly, we had to deal with the COVID-19 outbreak, which escalated in this time frame, considering how it presents high unresponsive fever and lung involvement as the most frequent symptoms.…”
Section: Discussionsupporting
confidence: 92%
“…One of the main contributors to morbidity and mortality among lung transplant recipients is BOS and one study analyzing 155 lung transplant recipients showed a strong association between the development of BOS and allograft colonization with Pseudomonas aeruginosa [18]. Pseudomonas aeruginosa has also been associated with humoral rejection and the development of donors-specific antibodies [19]. S. aureus is also another frequent cause of nosocomial pneumonia, as well as Gram-negative bacteria such as Acinetobacter spp.…”
Section: Bacterial Infectionsmentioning
confidence: 99%
“…70 Another notable finding that has recently emerged is the identification of an independent association between the isolation of Pseudomonas aeruginosa from respiratory specimens and the development of DSA. 71 This provides a new understanding of potential mechanism for crosstalk between innate and alloimmune responses and identifies a potential therapeutic target to prevent the development of DSA. 71,72 Diagnosis: Alternative methods for diagnosis are currently being investigated, including donor-derived cell-free DNA (ddcfDNA) and transcriptome analysis.…”
Section: Future Areas Of Developmentmentioning
confidence: 99%
“…71 This provides a new understanding of potential mechanism for crosstalk between innate and alloimmune responses and identifies a potential therapeutic target to prevent the development of DSA. 71,72 Diagnosis: Alternative methods for diagnosis are currently being investigated, including donor-derived cell-free DNA (ddcfDNA) and transcriptome analysis. Similar to the technology used in prenatal screening, circulation of donor DNA in the serum of recipients can be found after allograft injury with cell apoptosis.…”
Section: Future Areas Of Developmentmentioning
confidence: 99%